Autologous fat graft in irradiated orbit postenucleation for retinoblastoma. (3rd September 2018) - Klinger, Francesco; Maione, Luca; Vinci, Valeriano; Lisa, Andrea; Barbera, Federico; Balia, Laura; Caviggioli, Fabio; Maria, Alessandra Di
ABSTRACT: Autologous fat grafting has been extensively and successfully adopted in a number of pathologic conditions in regenerative surgery especially on irradiated fields in order to improve pain symptoms and tissue trophism promoting scar release. In the present study, we report our experience with autologous fat grafting for the treatment of postirradiation fibrosis and pain on three consecutive patients undergoing orbital enucleation for locally advanced retinoblastoma (RB) and subsequent radiotherapy. We selected three consecutive patients who underwent orbital enucleation for locally advanced RB and subsequent local radiotherapy showing severe reduction in orbital volume and eyelid length and retraction due to fibrosis, spontaneous local pain exacerbated after digital pressure with no possibility to place an ocular implant. They underwent autologous fat grafting in the orbital cavity and results were evaluated by clinical examination at 5 and 14 days, and 1, 3, 6 months, and 1 year after surgery. A significant release of scar retraction, reduction of fibrosis and orbital rim contraction together with an important improvement of pain symptoms was observed in all patients. The local changes observed enabled an ease placement of an ocular prosthetic implant (implant). No local or systemic complication occurred. Fat grafting is a promising treatment for patients showing radiotherapy related complication in the orbital area and it should be adopted by all oculoplastic surgeon in order to improve pain syndrome creating the ideal local conditions for the placement of an ocular prosthetic implant.